2017
DOI: 10.21037/qims.2017.06.08
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of epicardial fat volume: effects of scanning protocol and reproducibility of measurements in non-contrast cardiac CT vs. coronary CT angiography

Abstract: Background: Several studies have focused on the role of epicardial fat in the pathogenesis of cardiovascular disease (CVD). The main purpose of the study was to evaluate a computerized method for the quantitative analysis of epicardial fat volume (EFV) by non-contrast cardiac CT (NCT) for coronary calcium scan and coronary CT angiography (coronary CTA). Conclusions: Both NCT and coronary CTA can be used with low intra-and inter-observer variability for computer-assisted measurements of EFV. Cardiac CT may allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The automated measurement of epicardial fat volume also provides reliable intrareader measurements (intraclass correlation coefficient [ICC] 0.97] and interobserver measurements (ICC 0.98) 21 . This is in line with previous noncontrast CT studies which have demonstrated comparable inter‐ and intraobserver reproducibility 22,23 …”
Section: Methodssupporting
confidence: 82%
“…The automated measurement of epicardial fat volume also provides reliable intrareader measurements (intraclass correlation coefficient [ICC] 0.97] and interobserver measurements (ICC 0.98) 21 . This is in line with previous noncontrast CT studies which have demonstrated comparable inter‐ and intraobserver reproducibility 22,23 …”
Section: Methodssupporting
confidence: 82%
“…Technical developments in medical imaging techniques have led to significant improvements in the diagnostic performance of less-invasive imaging modalities such as computed tomography (CT), magnetic resonance imaging (MRI), nuclear medicine and ultrasound. Quantitative analysis of these imaging modalities allows for detection and diagnosis of various diseases with high accuracy (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Despite promising results available in the literature, traditional two-dimensional (2D) and three-dimensional (3D) visualization tools are still limited to a 2D screen, which affect realistic visualization of anatomical structures and pathologies of 3D datasets, and this is particularly apparent when dealing with complex pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of preventive medicine, the morbidity of coronary artery disease (CAD) is under control to a certain extent; however, the mortality of CAD remains a major problem worldwide (1)(2)(3)(4). Besides, obesity is considered a challenging public problem (5), which has been proven to be closely associated with CAD (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%